Hemikolektomie bei Kolonischämie: Fallbericht von Schweinegrippe mit letalem Verlauf - Vernadakis, S. (Chirurg, 2010)
Pandemic influenza A (H1N1) virus infection is rapidly spreading and has also become a common problem in Germany. Many cases with severe clinical presentation and death have been documented, especially in persons with underlying medical conditions. As of December 15, 2009, Germany has reported 119 H1N1-associated deaths. We report here the first H1N1-associated death in Germany, a 36-year-old woman with morbid obesity. The patient underwent a laparotomy with colon resection due to colon ischemia, a rare visceral complication in such cases. In this article an attempt has been made to reflect the state of requirements in terms of safety, occupational health, hygiene and working conditions with respect to activities involving logistics in the diagnostics, treatment (also surgical) and handling of such patients. Given the rapidly evolving nature the outbreak of human infection with the novel influenza A (H1N1) virus, influenza vaccination is recommended as the only way to prevent the infection of health care workers and patients with underlying medical conditions.